Developing effective communication skills in audiology using anonymous patient feedback - Bowers, Patrick; Graydon, Kelley (International journal of audiology, 2025)
To explore the value of anonymous patient feedback for audiology students, examining alignment between student and patient judgments on communication skills and assessing how students utilise the feedback. This study utilised a mixed methods design, employing a Likert survey to collect patient and student ratings on professionalism, compassion, and listening and talking skills in clinical encounters. Semi-structured interviews investigated the student perspective of receiving patient feedback. 13 Audiology students and 31 patients who were placed at, or received care at an Audiology teaching clinic. Patients' ratings across all measures were higher on average when compared to students' self-ratings, only correlating significantly for the measure concerning students' talking skills. Five themes and one subtheme were identified: Emotional impacts, A worthwhile experience, Contrasting priorities, Patients retake centre stage, and Self-reflective learners (subtheme Self-doubt). This study reveals that patient feedback led student Audiologists to report heightened seriousness in their interactions and increased attention on skills vital for patient-centred care. The process boosted students' confidence and reinforced awareness of the patient's perspective. Further research is needed to gauge the extent of these effects and explore the feasibility of implementing a large-scale patient feedback program in audiology training settings.